Bromoform exposure is associated with non-melanoma skin cancer: evidence from NHANES 2011–2020 - Gao, Mingnan; Guo, Han; Han, Jingjing; Liu, Jinhua; Hou, Yinglong; Wang, Zimao; Yang, Zheng; Wang, Qiying (Frontiers in Public Health, 2023)
Background Non-melanoma skin cancer (NMSC) is a prevalent skin malignancy. It has been indicated in many studies that trihalomethanes (THMs) exposure has a strong association with tumors but has not been associated with NMSC. Our investigation aims to explore the association between THMs exposure and NMSC. Methods Cross-sectional data from the 2011 to 2020 National Health and Nutrition Examination Survey (NHANES) was collected. Poisson regression and subgroup analyses were performed to evaluate the association between individual THMs components and NMSC. Fitted smoothing curves and generalized additive models were also used. Results This study involved 5,715 individuals, 98 (1.7%) of whom self-reported NMSC. After adjusting for covariates, Poisson regression showed that higher blood TBM levels were associated with an increased likelihood of NMSC (OR = 1.03; 95% CI: 1.01–1.05, p = 0.002). However, the correlation between the blood levels of TCM, DBCM, and BDCM and the likelihood of NMSC was not statistically significant (all p > 0.05). Subgroup analysis and interaction tests showed no significant differences between blood TBM concentration and the likelihood of NMSC, indicating that age, gender, and race were significantly independent of this positive association (all p < 0.05). Conclusions Our results implied that among adults older than 65 years old in the U.S., elevated blood TBM concentrations were positively associated with NMSC. More prospective investigations are required to validate this relationship with the early prevention of NMSC.